PARADOX AND TRANSFORMATION - Nancy C. Maryboy; David H. Begay; Lee Nichol (Unmas Press, 2020)
The English term “paradox” is suggestive of a particular Indigenous value of perceiving and understanding in terms of balancing opposites. Paradox thinking points to a series of concepts central to traditional Navajo epistemology and ontology: complementarity, dynamic movement, cyclical balance, and transformation. This matrix of traditional wisdom is positioned in relation to western empiricism – especially the latter’s expression as problem-solving and critical thinking methodologies. It is suggested that one aspect of transformation involves re-visioning the relationship between these two cognitive styles.